2020
DOI: 10.1038/s41598-019-57055-w
|View full text |Cite
|
Sign up to set email alerts
|

Classifying superconductivity in Moiré graphene superlattices

Abstract: Several research groups have reported on the observation of superconductivity in bilayer graphene structures where single atomic layers of graphene are stacked and then twisted at angles forming Moiré superlattices. The characterization of the superconducting state in these 2D materials is an ongoing task. Here we investigate the pairing symmetry of bilayer graphene Moiré superlattices twisted at  = 1.05°, 1.10° and 1.16° for carrier doping states varied in the range of = 0.5 − 1.5 • 10 12 −2 (where superco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 64 publications
(154 reference statements)
0
60
0
Order By: Relevance
“…The rotation is carried out starting from two perfectly AA stacked graphene layers and rotating around an axis orthogonal to the layers and passing through two C atoms, one on top of the other, belonging to the two planes (that therefore preserve their initial AA stacking). The respective structures can also be classified, according to the notation commonly used in the literature [55], using the pair of indexes (n, m): (31,30), (21,20), (13,12), and (9,8) Sampling of the Brillouin zone (BZ) for the self-consistent (SCF) calculations was restricted at the point for all four systems; no significant changes were observed after increasing the size of the sampling of the BZ for the smaller supercells. Single-particle energies at other points in the BZ were obtained by non-SCF calculations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rotation is carried out starting from two perfectly AA stacked graphene layers and rotating around an axis orthogonal to the layers and passing through two C atoms, one on top of the other, belonging to the two planes (that therefore preserve their initial AA stacking). The respective structures can also be classified, according to the notation commonly used in the literature [55], using the pair of indexes (n, m): (31,30), (21,20), (13,12), and (9,8) Sampling of the Brillouin zone (BZ) for the self-consistent (SCF) calculations was restricted at the point for all four systems; no significant changes were observed after increasing the size of the sampling of the BZ for the smaller supercells. Single-particle energies at other points in the BZ were obtained by non-SCF calculations.…”
Section: Methodsmentioning
confidence: 99%
“…The correlated insulating phase is attributed to enhanced electron-electron interaction within the FBs [14,15], although some authors are highlighting the relevance of the electron-phonon interaction [16][17][18][19]. After electrostatic doping, achieved by gating the structure, unconventional superconductivity with a critical temperature ranging from 1.7 to 3 K appears in a strong pairing regime, with a phase diagram very similar to that of the underdoped cuprates, whose origin is still to be understood [17,20].…”
Section: Introductionmentioning
confidence: 99%
“…As Raman spectroscopy experiments have revealed, BLG systems can support two phonon modes [5][6][7][8][9][10][11][12][13][14][15], one corresponding to intralayer vibrations and the other to interlayer vibrations. In this spirit, a two-gap superconductivity has been proposed and studied for displaced and commensurate twisted BLG systems [53,56,57]. It was found that, depending on the original stacking order of BLG (being either AA or AB) and the magnitude of the chemical potential, a small in-plane displacement of the pristine layers with respect to each other can drive s-wave and p-wave pairing symmetries into d-wave and f -wave symmetry classes, respectively, and increase the superconducting critical temperature [53].…”
mentioning
confidence: 99%
“…where ( ) = ; polar configuration (15) ( ) = √1 − 2 ; axial configuration (16) More details about the Jc(sf,T) analysis for p-wave symmetry can be found elsewhere [26,27]. This approach is recently applied for wide range of thin film unconventional superconductors [23,24,[26][27][28][29][30][31][32].…”
Section: Models Descriptionmentioning
confidence: 99%